PENGEMBANGAN PROGRAM PENINGKATAN KOMPETENSI GURU SEKOLAH DASAR DALAM PEMBELAJARAN TEMATIK DI KELAS RENDAH MELALUI ASESMEN PORTOFOLIO - Ason Ason (STKIP Melawi, 2014)
Abstract: This study aims to design the development of Elementary School Teachers Competency Enhancement Program in Thematic Learning at Lower Grade Through Portfolio Assessment . In detail, these objectives can be formulated as follows: 1). To determine the competence of beginning elementary school teachers on thematic learning and their understanding of the assessment portfolio. 2 . To develop teachers' understanding of thematic learning through portfolio assessment in accordance with the development of low-grade participants didi Elementary School. 3). To develop the skills of teachers in preparing lesson planning, implementing and assessing the thematic learning. 4). Teachers can develop thematic learning through portfolio assessment that can improve students' science process skills. The results of the initial competency questionnaire on trainee teachers, both in the control group and the experimental group showed that the implementation of thematic learning curriculum in elementary school in Nanga Pinoh District Melawi Regency has not accomplished in accordance with the purpose of the curriculum. The thematic learning competency of Low-grade elementary school teacher in Nanga Pinoh District still needs to be improved. This is indicated by the results of a questionnaire that presents a number of 2.46 for experimental group and 2.13 for the the control group. With these figures, both the experimental group and the control group both at qualification enough . While the results of the teacher competencies after training questionnaire, both the control group and the experimental group showed a significant increase. From the test results showed that the value of 3.34 for the experimental group and the control group of 3.10 , and both are in good and satisfactory qualification. The presence of significant developments between competence questionnaire results showed that the beginning and end of the training model designed by researchers in order to improve the competence of teachers is quite successful and hit the target. The model of the training program is to improve elementary school teachers' competence in thematic learning through portfolio assessment. This is supported by the results of the assessment portfolio to document learning steps thematic, thematic syllabus and lesson plans as well as the implementation of thematic learning in the classroom. Of the recapitulation of all components of the assessment and the assessment showed that the scores of participants is quite high, reaching 3.29. This means that the training qualification was good and satisfying .Key Words: Teacher Competency Enhancement Programme, Thematic learning, Portfolio.Abstrak: Penelitian ini bertujuan untuk mendesain pengembangan program peningkatan kompetensi guru sekolah dasar dalam pembelajaran tematik di kelas rendah melalui asesmen portofolio. Secara rinci tujuan tersebut dapat dirumuskan sebagai berikut: 1) Untuk mengetahui kompetensi awal guru-guru sekolah dasar tentang pembelajaran tematik dan pemahaman mereka mengenai asesmen portofolio; 2) Untuk mengembangkan pemahaman guru tentang pembelajaran tematik melalui asesmen portofolio yang sesuai dengan perkembangan peserta didik kelas rendah sekolah dasar; 3) Untuk mengembangkan keterampilan guru dalam menyusun perencanaan pembelajaran, melaksanakannya, dan melakukan penilaian dalam pembelajaran tematik; 4) Guru dapat mengembangkan pembelajaran tematik melalui asesmen portofolio sehingga dapat meningkatkan keterampilan proses sains siswa. Hasil angket kompetensi awal pada guru peserta pelatihan, baik pada kelompok kontrol maupun kelompok eksperiman menunjukkan bahwa implementasi kurikulum pembelajaran tematik di SD Kecamatan Nanga Pinoh Kabupaten Melawi belum terlaksana sesuai dengan maksud kurikulum tersebut. Kompetensi guru kelas rendah SD se-Kecamatan Nanga Pinoh tentang pembelajaran tematik masih perlu ditingkatkan lagi. Hal ini ditunjukkan dengan hasil angket yang menyajikan angka 2,46 untuk kelompok eksperimen dan 2,13 untuk kelompok kontrol. Dengan angka tersebut, baik kelompok eksperimen maupun kelompok kontrol keduanya berada pada kualifikasi cukup. Sementara hasil angket kompetensi akhir yang dimiliki guru peserta pelatihan, setelah mengikuti pelatihan, baik pada kelompok kontrol maupun kelompok eksperiman menunjukkan adanya peningkatan yang signifikan. Dari hasil tes akhir menunjukkan bahwa nilai untuk kelompok eksperimen sebesar 3,34 dan untuk kelompok kontrol sebesar 3,10 serta keduanya berada pada kualifikasi baik dan memuaskan. Adanya perkembangan yang signifikan antara hasil angket kompetensi awal dan akhir menunjukkan bahwa model pelatihan yang dirancang oleh peneliti dalam rangka meningkatkan kompetensi guru cukup berhasil dan mengena sasaran. Model pelatihan dimaksud adalah mengacu pada program peningkatan kompetensi guru sekolah dasar dalam pembelajaran tematik melalui asesmen portofolio. Hal ini didukung oleh hasil asesmen portofolio terhadap dokumen langkah-langkah pembelajaran tematik, silabus dan RPP tematik serta implementasi pembelajaran tematik di kelas. Dari hasil rekapitulasi semua komponen penilaian dan asesmen menunjukkan bahwa skor peserta pelatihan cukup tinggi yakni mencapai 3,29. Ini berarti bahwa kualifikasi pelatihan ini baik dan memuaskan. Kata Kunci : program peningkatan kompetensi guru, pembelajaran tematik, portofolio.